Attitudes and knowledge towards breastfeeding in adolescent mothers users of a mother and child hospital. - Benancio Vigilio, Medalit Lenytha (2022)
Objective. To determine the relationship between attitudes and knowledgeto wards breast feeding in adolescent mothers users of theCentro Materno Infantil Carlos Showing Ferrari, Huánuco, 2021. Methods. This was ananalytical study with a quantitative approach and relational level. The census population consisted of 120 adolescent mothers. The technique appliedwas the individualized interview and the measurement instruments were aknowledge questionn aire and a Likert scale of attitudes, previously validated. The chi-square test was used for inferential analysis and ethical aspectswere taken into account. Results. When analyzing knowledge about breast feeding, 62.7% (62) showed sufficient knowledge, while 68.6% (70) showed positive attitudes when analyzing attitudes about breastfeeding. In the inferential analysis, no statistical significance was found betweenattitudes and knowledge about breastfeeding. Conclusions. There is no relationship between attitudes and knowledge towards breast feeding inadolescent mothers, so the null hypothesis was accepted.